Sintesis Ca2P2O7 dari Limbah Kerang dengan Metode Solvotherma: Faisal Akbar, Retno Kusumaningrum, Miraj S. Jamil, Alfian Noviyanto, Wahyu B. Widayatno, Agus S. Wismogroho, dan Nurul T. Rochman - Faisal Akbar Faisal Akbar; Retno Kusumaningrum Retno Kusumaningrum; Miraj S. Jamil Miraj S. Jamil; Alfian Noviyanto Alfian Noviyanto; Wahyu B. Widayatno Wahyu B. Widayatno; Agus S. Wismogroho Agus S. Wismogroho; Nurul T. Rochman Nurul T. Rochman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
Synthesize of calcium pyrophosphate (CPP) was made using solvothermal method followed by heat treatment. The source of calcium carbonate was green shells waste and blood clams waste. CaO was obtained by decompose calcium carbonate, which is from the green shells and blood clams, at 10000 C for 2 hours in air atmosphere. CaO powder was mixed with H3PO4 to synthesize CaHPO4 using solvothermal method. Single phase of calcium pyrophosphate was obtained from blood clams waste after heat treatment of CaHPO4 at 8000 C for 2 hours. However, impurity phases were observed for calcium pyrophosphate from green shells waste. Moreover, the average particle size of calcium pyrophosphate from green shells waste was 1.5 ± 0.8 µm, which is bigger compared to 258 ± 151 nm of blood clams waste.